RELIGIOUS AND SECULAR EDUCATION IN THE LITERATURE OF THE AFGHAN-AMERICAN DIASPORA: WOMAN, FAMILY AND SOCIETY (Scientific journal of the Fergana State University, 2024)
In this article, the works of Farooka Gauhari, Maryam Qudrat Aseel, Nelofar Pazira, and Saima Wahab, among the mature writers of the Afghan-American diaspora literature, are analyzed based on the criterion of artistic influence and its virtues, and their artistic characteristics are revealed. Afghanistan is the main theme in every writerʼs work, the social lifestyle of Afghans in the pre-war, Taliban and post-war periods, especially the role of women in society and family, is skillfully described. In its place, education is divided into religious and secular aspects, religious education shows a connection with Afghanistan, and secular education shows a connection with America. If they seek their identity, values and historical origin through religion, from a modern point of view, the fate of today and tomorrow in American society is guaranteed only by acquiring a secular education. In the works of Afghan-American literary figures, it describes the commonality of religious and secular education in womenʼs education, the conflicting traditions of the West and the East, and the commonality and uniqueness of the customs of the two nations. Afghan writers writing in English praised religious and secular ideas without denying the culture and values of both countries.